High-toughness solid waste-based concrete and preparation method thereof
By using modified regenerated aggregate and modified basalt fibers in all solid waste concrete, combined with interface improvement technology of graphene and silane coupling agent, the problem of insufficient research on the strength and toughness of all solid waste concrete has been solved, and it has been significantly improved. Compression, flexural and crack resistance.
Patent Information
- Application Number
- CN202411342490.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-25
AI Technical Summary
In the prior art, there are few researches on the strength and toughness modification of all solid waste concrete, and it is difficult to improve its bending crack resistance and tensile strength.
Using solid waste-based gelling materials and modified recycled aggregates as the main materials, modified basalt fibers and alkali-resistant penetration agents are added to improve interfacial adhesion through graphene and silane coupling agents, and etching basalt fibers with alkaline liquid to improve the surface Roughness, graft copolymerization reaction of carboxymethylcellulose and caprolactam, reduces the capillary pressure of the regenerated aggregate and enhances the mechanical properties of the concrete.
It significantly improves the compressive strength, flexural strength and fracture energy of concrete, enhances crack resistance, and improves the all-round mechanical properties of concrete.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a high-toughness solid waste-based concrete and a preparation method thereof. Background Art
[0003] Solid waste-based concrete is a concrete that mostly uses solid waste-based cementitious materials as cementitious materials, and uses slag, tailings sand, tailings waste rock, etc. as aggregates. Solid waste-based cementitious materials generally refer to industrial and mining wastes with potential hydraulic and volcanic ash properties, such as fly ash, granulated blast furnace slag powder, steel slag, desulfurized gypsum, and alkali slag. In general, these materials are used as active mixed materials or active admixtures in a certain amount and proportion in the production of cement and the mixing process of concrete, which can not only ensure the workability, strength and durability of cement concrete, but also reduce costs.
[0004] The method of strengthening and toughening ordinary cement concrete is to modify it with fibers. Some will also use other modified substances to improve the interface between the cement matrix and the fibers to obtain better adhesion. Solid waste-based concrete has similar properties to ordinary concrete, with high compressive strength and low tensile strength. Therefore, improving its flexural crack toughness and tensile strength has important engineering significance. However, there are relatively few studies on the modification of all-solid waste concrete to strengthen and toughen it. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a high-toughness solid waste-based concrete, which adopts solid waste-based cementitious materials and modified recycled aggregates as main materials to achieve the recycling of industrial solid waste, and adds modified basalt fibers and alkali-resistant penetrants to improve the mechanical properties and crack resistance of concrete.
[0006] Specifically, the high-toughness solid waste-based concrete of the present invention is composed of the following raw materials in parts by weight: 200-250 parts of solid waste-based cementitious materials, 500-800 parts of modified recycled aggregates, 30-40 parts of activators, 2-4 parts of modified basalt fibers, 2-5 parts of water reducers, 0.2-0.4 parts of alkali-resistant penetrants, and 80-100 parts of water.
[0007] Preferably, the solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of (1-2):(6-8):(1-3).
[0008] Preferably, the mineral powder grade is S95 or S105, and the fly ash grade is grade I or grade II.
[0009] Preferably, the modified recycled aggregate preparation process is: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is (2-5):(0.4-0.6):(1-2):1000. The present invention utilizes graphene and silane coupling agent to improve the interface of recycled aggregate, facilitates the attachment of hydration products with gelling property, reduces the water-binder ratio of the interface transition zone, improves the strength of the interface transition zone, and can enhance the strength of concrete materials.
[0010] Preferably, the recycled aggregate includes recycled fine aggregate and recycled coarse aggregate. More preferably, the mass ratio of recycled fine aggregate to recycled coarse aggregate is 1:1-1.8. More preferably, the recycled aggregate is obtained by crushing and screening waste concrete.
[0011] Preferably, the mass concentration of the graphene dispersion is 12-20%.
[0012] Preferably, the activator is a mixture of red mud and desulfurized gypsum in a mass ratio of (4-6): (3-4). In order to treat large amounts of solid waste generated by the mining industry and the construction industry, reduce carbon emissions and the use of natural sand and stone materials, the present invention uses siliceous and aluminum-based active materials such as steel slag produced by converter steelmaking, blast furnace slag produced by blast furnace ironmaking, and fly ash produced by coal-fired power plants as cementitious materials, desulfurized gypsum produced by treating sulfur dioxide in coal combustion flue gas and red mud, a waste of the aluminum industry, as alkaline activators for providing an alkaline environment and sulfate ions, and recycled aggregates obtained by crushing and screening waste concrete as coarse and fine aggregates to prepare solid waste-based concrete.
[0013] The modified basalt fiber preparation process is: alkali solution is used to etch the basalt fiber, and then the basalt fiber is cleaned and dried. The present invention strengthens the basalt fiber concrete to improve the mechanical properties, and alkali is used to etch the surface of the basalt fiber to improve its surface roughness, thereby improving the interface and enhancing the bonding with the solid waste-based concrete matrix.
[0014] Preferably, the alkali solution is sodium hydroxide solution.
[0015] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and solvent into a reaction kettle, mix them evenly, introduce nitrogen and then heat up, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat and stir to obtain the product, wherein the mass ratio of caprolactam, solvent, carboxymethyl cellulose, sodium hydroxide and acyl chloride is (10-12):(45-50):(1-2):(0.02-0.05):(0.04-0.05). The present invention can reduce the capillary pressure of the recycled aggregate through the graft copolymerization of carboxymethyl cellulose and caprolactam, which is conducive to the solution containing the cementitious material and the activator to enter the pores, generate a hydration reaction, fill the gaps, strengthen the recycled aggregate, and improve the toughness of the solid waste-based concrete.
[0016] Preferably, the solvent is water. It should be noted that the water here is a solvent added for preparing the alkali-resistant penetrant and is not included in the water dosage in the concrete formula, and the two have nothing to do with each other.
[0017] Preferably, in the preparation process of the alkali-resistant penetrant, the temperature is raised to 70-80° C. after nitrogen is introduced, and then heated to 120-150° C. and stirred for 5-6 hours.
[0018] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.
[0019] The present invention also relates to a method for preparing the above-mentioned high-toughness solid waste-based concrete, which specifically comprises the following steps:
[0020] 1) Weigh each raw material by mass,
[0021] 2) Mix all the raw materials evenly, shape them, and cure them to obtain the product.
[0022] Preferably, the curing adopts standard curing. DETAILED DESCRIPTION
[0023] In order to prove the technical effect of the present invention, high-toughness solid waste-based concrete was prepared and standardly cured to the specified age for mechanical property testing. The raw materials used were S95 grade mineral powder, grade II fly ash, polycarboxylate water reducer with a water reduction rate of 28%, recycled aggregate came from waste concrete, which was a mixture of recycled fine aggregate and recycled coarse aggregate with a mass ratio of 1:1.5, and the mass concentration of graphene dispersion was 15%.
[0024] Example 1
[0025] High-toughness solid waste-based concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of modified recycled aggregates, 40 parts of activators, 4 parts of modified basalt fibers, 4 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 95 parts of water.
[0026] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0027] The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is 2:0.5:1:1000.
[0028] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0029] The modified basalt fiber preparation process is as follows: basalt fiber is etched with sodium hydroxide solution, cleaned and dried to obtain the modified basalt fiber.
[0030] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and water into a reaction kettle, mix them evenly, introduce nitrogen and heat to 70°C, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat to 130°C and stir for 5 hours, wherein the mass ratio of caprolactam, water, carboxymethyl cellulose, sodium hydroxide and acyl chloride is 11:46:2:0.03:0.05.
[0031] After testing, the 28d compressive strength of concrete was 43.4MPa, the 28d flexural strength was 6.8MPa, the 56d compressive strength was 46.3MPa, and the fracture energy was 354.7N / m.
[0032] Example 2
[0033] High-toughness solid waste-based concrete is composed of the following raw materials in parts by weight: 220 parts of solid waste-based cementitious materials, 800 parts of modified recycled aggregates, 34 parts of activators, 4 parts of modified basalt fibers, 3 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 90 parts of water.
[0034] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 2:8:1.
[0035] The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is 4:0.6:1:1000.
[0036] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 6:3.
[0037] The modified basalt fiber preparation process is as follows: basalt fiber is etched with sodium hydroxide solution, cleaned and dried to obtain the modified basalt fiber.
[0038] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and water into a reaction kettle, mix them evenly, introduce nitrogen and heat to 70°C, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat to 130°C and stir for 5 hours, wherein the mass ratio of caprolactam, water, carboxymethyl cellulose, sodium hydroxide and acyl chloride is 12:44:1.5:0.03:0.05.
[0039] After testing, the 28d compressive strength of concrete was 42.3MPa, the 28d flexural strength was 6.6MPa, the 56d compressive strength was 45.8MPa, and the fracture energy was 351.5N / m.
[0040] Comparative Example 1
[0041] Concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of recycled aggregates, 40 parts of activators, 4 parts of modified basalt fibers, 4 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 95 parts of water.
[0042] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0043] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0044] The modified basalt fiber preparation process is as follows: basalt fiber is etched with sodium hydroxide solution, cleaned and dried to obtain the modified basalt fiber.
[0045] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and water into a reaction kettle, mix them evenly, introduce nitrogen and heat to 70°C, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat to 130°C and stir for 5 hours, wherein the mass ratio of caprolactam, water, carboxymethyl cellulose, sodium hydroxide and acyl chloride is 11:46:2:0.03:0.05.
[0046] After testing, the 28d compressive strength of concrete was 37.5MPa, the 28d flexural strength was 5.4MPa, the 56d compressive strength was 40.3MPa, and the fracture energy was 341.0N / m.
[0047] Comparative Example 2
[0048] Concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of modified recycled aggregates, 40 parts of activators, 4 parts of modified basalt fibers, 4 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 95 parts of water.
[0049] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0050] The modified recycled aggregate preparation process is as follows: adding a silane coupling agent to a graphene dispersion, mixing the mixture evenly, and then spraying the mixture onto the surface of the recycled aggregate to obtain the modified recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, and recycled aggregate is 2:0.5:1000.
[0051] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0052] The modified basalt fiber preparation process is as follows: basalt fiber is etched with sodium hydroxide solution, cleaned and dried to obtain the modified basalt fiber.
[0053] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and water into a reaction kettle, mix them evenly, introduce nitrogen and heat to 70°C, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat to 130°C and stir for 5 hours, wherein the mass ratio of caprolactam, water, carboxymethyl cellulose, sodium hydroxide and acyl chloride is 11:46:2:0.03:0.05.
[0054] After testing, the 28d compressive strength of concrete was 38.2MPa, the 28d flexural strength was 5.1MPa, the 56d compressive strength was 41.7MPa, and the fracture energy was 345.3N / m.
[0055] Comparative Example 3
[0056] Concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of modified recycled aggregates, 40 parts of activators, 4 parts of polyvinyl alcohol fibers, 4 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 95 parts of water.
[0057] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0058] The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is 2:0.5:1:1000.
[0059] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0060] The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and water into a reaction kettle, mix them evenly, introduce nitrogen and heat to 70°C, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat to 130°C and stir for 5 hours, wherein the mass ratio of caprolactam, water, carboxymethyl cellulose, sodium hydroxide and acyl chloride is 11:46:2:0.03:0.05.
[0061] After testing, the 28d compressive strength of concrete was 35.6MPa, the 28d flexural strength was 4.9MPa, the fibers were pulled out when the specimen broke, the 56d compressive strength was 38.1MPa, and the fracture energy was 330.4N / m.
[0062] Comparative Example 4
[0063] Concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of modified recycled aggregates, 40 parts of activators, 4 parts of modified basalt fibers, 4 parts of water reducing agents, and 95 parts of water.
[0064] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0065] The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is 2:0.5:1:1000.
[0066] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0067] The modified basalt fiber preparation process comprises the following steps: etching the basalt fiber with a sodium hydroxide solution, washing and drying the basalt fiber.
[0068] After testing, the 28d compressive strength of concrete was 31.8MPa, the 28d flexural strength was 4.2MPa, the 56d compressive strength was 35.3MPa, and the fracture energy was 307.5N / m.
[0069] Comparative Example 5
[0070] Concrete is composed of the following raw materials in parts by weight: 240 parts of solid waste-based cementitious materials, 780 parts of modified recycled aggregates, 40 parts of activators, 4 parts of modified basalt fibers, 4 parts of water reducers, 0.3 parts of alkali-resistant penetrants, and 95 parts of water.
[0071] The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of 1:8:2.
[0072] The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is 2:0.5:1:1000.
[0073] The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of 4:4.
[0074] The modified basalt fiber preparation process is as follows: basalt fiber is etched with sodium hydroxide solution, cleaned and dried to obtain the modified basalt fiber.
[0075] The alkali-resistant penetrant is potassium methyl silicate.
[0076] After testing, the 28d compressive strength of concrete was 33.4MPa, the 28d flexural strength was 3.9MPa, the 56d compressive strength was 36.1MPa, and the fracture energy was 320.7N / m.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-toughness solid waste-based concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 200-250 parts of solid waste-based cementitious materials, 500-800 parts of modified recycled aggregates, 30-40 parts of activators, 2-4 parts of modified basalt fibers, 2-5 parts of water reducers, 0.2-0.4 parts of alkali-resistant penetrants, and 80-100 parts of water. The solid waste-based cementitious material is composed of steel slag powder, mineral powder and fly ash in a mass ratio of (1-2):(6-8):(1-3). The modified recycled aggregate preparation process is as follows: adding silane coupling agent and acrylic emulsion to graphene dispersion, mixing evenly and spraying the mixture onto the surface of recycled aggregate to obtain the modified recycled aggregate, wherein the mass ratio of graphene, silane coupling agent, acrylic emulsion and recycled aggregate is (2-5):(0.4-0.6):(1-2):1000. The activator is a mixture of red mud and desulfurized gypsum in a mass ratio of (4-6):(3-4), The modified basalt fiber preparation process is as follows: basalt fiber is etched with alkali solution, cleaned and dried to obtain the modified basalt fiber. The preparation process of the alkali-resistant penetrant is as follows: add caprolactam and solvent into a reaction kettle, mix them evenly, introduce nitrogen and then heat up, add carboxymethyl cellulose, sodium hydroxide and acyl chloride, heat and stir to obtain the alkali-resistant penetrant, wherein the mass ratio of caprolactam, solvent, carboxymethyl cellulose, sodium hydroxide and acyl chloride is (10-12):(45-50):(1-2):(0.02-0.05):(0.04-0.05).
2. The high-toughness solid waste-based concrete according to claim 1, characterized in that: The mineral powder grade is S95 or S105, and the fly ash grade is grade I or grade II.
3. The high-toughness solid waste-based concrete according to claim 1, characterized in that: The recycled aggregate includes recycled fine aggregate and recycled coarse aggregate.
4. The high-toughness solid waste-based concrete according to claim 3, characterized in that: The mass ratio of recycled fine aggregate to recycled coarse aggregate is 1:1-1.
8.
5. The high-toughness solid waste-based concrete according to claim 1, characterized in that: The alkali solution is sodium hydroxide solution.
6. The high-toughness solid waste-based concrete according to claim 1, characterized in that: The solvent is water.
7. The high-toughness solid waste-based concrete according to claim 1, characterized in that: In the preparation process of the alkali-resistant penetrant, nitrogen is introduced and the temperature is raised to 70-80°C, and then heated to 120-150°C and stirred for 5-6 hours.
8. The high-toughness solid waste-based concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.
9. The method for preparing high-toughness solid waste-based concrete according to any one of claims 1 to 8, characterized in that: The steps include: 1) Weigh each raw material by mass, 2) Mix all the raw materials evenly, shape them, and cure them to obtain the product.
10. The preparation method according to claim 9, characterized in that: The maintenance described adopts standard maintenance.
Citation Information
Patent Citations
Modified recycled concrete and preparation method thereof
CN109354464A
Special grouting material for bridge repair
CN111533525A
Recycled concrete and preparation method thereof
CN112250374A
High-strength recycled concrete and preparation method thereof
CN113321470A
Enhancement regulator for machine-made sand concrete and concrete
CN113800810A
Cited By
Solid waste-based conductive recycled aggregate high-ductility concrete and preparation method thereof
CN120058296A
Preparation method and application of carbon sequestration concrete reclaimed material high-elasticity powder cementing material
CN120157445A
Green low-carbon cementing material for roadbed and preparation method of green low-carbon cementing material
CN120590136A
